Geographical and Seasonal Thermal Sensitivity of Grazing Pressure by Microzooplankton in Contrasting Marine Ecosystems - Cabrerizo, Marco J.; Marañón, Emilio (Frontiers in Microbiology, 2021)
Grazing pressure, estimated as the ratio between microzooplankton grazing and phytoplankton growth rates (g:μ), is a strong determinant of microbial food-web structure and element cycling in the upper ocean. It is generally accepted that g is more sensitive to temperature than μ, but it remains unknown how the thermal dependence (activation energy, Ea) of g:μ varies over spatial and temporal scales. To tackle this uncertainty, we used an extensive literature analysis obtaining 751 paired rate estimates of μ and g from dilution experiments performed throughout the world’s marine environments. On a geographical scale, we found a stimulatory effect of temperature in polar open-ocean (∼0.5 eV) and tropical coastal (∼0.2 eV) regions, and an inhibitory one in the remaining biomes (values between −0.1 and −0.4 eV). On a seasonal scale, the temperature effect on g:μ ratios was stimulatory, particularly in polar environments; however, the large variability existing between estimates resulted in non-significant differences among biomes. We observed that increases in nitrate availability stimulated the temperature dependence of grazing pressure (i.e., led to more positive Ea of g:μ) in open-ocean ecosystems and inhibited it in coastal ones, particularly in polar environments. The percentage of primary production grazed by microzooplankton (∼56%) was similar in all regions. Our results suggest that warming of surface ocean waters could exert a highly variable impact, in terms of both magnitude and direction (stimulation or inhibition), on microzooplankton grazing pressure in different ocean regions.